2014
DOI: 10.1016/j.febslet.2014.06.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐141 promotes the proliferation of non‐small cell lung cancer cells by regulating expression of PHLPP1 and PHLPP2

Abstract: The dysregulation of microRNAs (miRNAs) is crucially implicated in the development of various cancers. In this study, we explored the biological role of miR‐141 in non‐small cell lung cancer (NSCLC). miR‐141 expression was significantly up‐regulated in NSCLC tissues, and its overexpression accelerated NSCLC cell proliferation in vitro and tumor growth in vivo. We subsequently identified the antagonists of PI3K/AKT signaling, PH domain leucine‐rich‐repeats protein phosphatase 1 (PHLPP1) and PHLPP2, as direct ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 29 publications
4
45
1
Order By: Relevance
“…Inversely, in the present study, microRNA-141 level was 1.97-fold higher in NSCLC (all n = 125: SCC n = 23, ADC n = 101, and LCC n = 1) than in the paired adjacent non-cancerous lung tissues. These results were concordant with the studies with small size of NSCLC patients (all n = 70: SCC n = 36 and ADC n = 34) (Liu et al 2012) and NSCLC (n = 12) (Mei et al 2014). The number of SCC may be a factor for the contradicting results.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Inversely, in the present study, microRNA-141 level was 1.97-fold higher in NSCLC (all n = 125: SCC n = 23, ADC n = 101, and LCC n = 1) than in the paired adjacent non-cancerous lung tissues. These results were concordant with the studies with small size of NSCLC patients (all n = 70: SCC n = 36 and ADC n = 34) (Liu et al 2012) and NSCLC (n = 12) (Mei et al 2014). The number of SCC may be a factor for the contradicting results.…”
Section: Discussionsupporting
confidence: 89%
“…The number of SCC may be a factor for the contradicting results. Since the studies of Liu et al (2012), Mei et al (2014) and ours were all based on Chinese NSCLC patients, it could be possible that microRNA-141 expression may be related to the race, e.g., microRNA-141 may play a different role in the NSCLC of yellow race and white race. However, this hypothesis needs to be verified and thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-141 was also found to down-regulate SOX17 expression and activate the WNT signal pathway, which promotes esophageal tumorigenesis [33]. Recently, Mei et al [34] reported miR-141 promoted the proliferation of non-small cell lung cancer cells by regulating expression of PHLPP1 and PHLPP2.…”
Section: Discussionmentioning
confidence: 99%